2016
DOI: 10.1161/circinterventions.115.002896
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Available Protocols for Aspirin Hypersensitivity for Patients Undergoing Percutaneous Coronary Intervention

Abstract: Available protocols for aspirin hypersensitivity are effective and safe, representing a feasible approach for patients needing dual antiplatelet therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…4 Despite the availability of disparate ASA desensitization protocols, 7,10-12 these are not commonly used in real-world practice. 6 Indeed, the fact that these may be time-consuming potential leading to treatment delays are potential causes for physicians to not embrace these protocols particularly in settings such as the treatment of patients with CAD. In patients with ASA hypersensitivity and concomitant CAD, data on the safety and efficacy of desensitization therapy are limited to small case series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Despite the availability of disparate ASA desensitization protocols, 7,10-12 these are not commonly used in real-world practice. 6 Indeed, the fact that these may be time-consuming potential leading to treatment delays are potential causes for physicians to not embrace these protocols particularly in settings such as the treatment of patients with CAD. In patients with ASA hypersensitivity and concomitant CAD, data on the safety and efficacy of desensitization therapy are limited to small case series.…”
Section: Discussionmentioning
confidence: 99%
“…Desensitization protocols generally involve gradual increases in patient exposure to ASA with the goal of mitigating or abolishing immune-mediated reaction. 4,6 However, many desensitization protocols require several days to be completed, making them unpractical. This may also contribute to the limited experience with applying ASA desensitization protocols in real-world practice in patients with CAD.…”
mentioning
confidence: 99%
“…However, in a recent systematic review survey [32], a surprising 56% of cardiologists do not perform challenge or desensitization procedures, but manage ASA hypersensitivity using alternative treatments. The most common monotherapy in this survey was clopidogrel.…”
Section: Discussionmentioning
confidence: 99%
“…This data has been confirmed by many observational studies, which have revealed a prevalence between 2.6% and 3.1%. 25 The mechanism underlying aspirin hypersensitivity reactions can be either immunological or pharmacological; however, some patients could have both reactions. Allergic/immunological reactions are due to a specific immunologlobulin E (IgE) produced against the drug, whereas pharmacological reactions are mediated by inhibition of the COX-1 pathway.…”
Section: Management Of Aspirin-intolerant Patientsmentioning
confidence: 99%
“…Once the desensitization protocol is completed, it is important to keep on assuming aspirin and not to interrupt it for more than 5 days in a row; otherwise, the upregulation of leukotriene receptors will make another desensitization procedure necessary (Table 2). 25 The ADAPTED Registry was the largest study exploring the systematic use of ASA desensitization in a large cohort of patients with CAD, both acute and stable, undergoing invasive evaluation with the intent to undergo PCI. A total of 330 patients were enrolled, including high coronary risk patients, such as patients with STEMI, and those who had a history of severe anaphylactic reactions, such as anaphylactic shock.…”
Section: Management Of Aspirin-intolerant Patientsmentioning
confidence: 99%